Multicentennial to millennial–scale changes in the East Asian summer monsoon during Greenland interstadial 25. (September 2022) - Dong, Jinguo; Shen, Chuan-Chou; Wang, Yi; Hu, Hsun-Ming; Banerjee, Yogaraj; Huang, Wei
Abstract: A multidecadal-resolved stalagmite δ 18 O record from two nearby caves, Lianhua and Dragon, in Shanxi Province, northern China, characterizes the detailed East Asian summer monsoon (EASM) intensity changes at 114.6–108.3 ka during Marine Oxygen Isotope Stage 5d. Our record shows an intensification of the EASM at 114.6–109.5 ka, followed by a rapid weakening at 109.5–108.4 ka. The millennial-scale strong monsoonal event appears to be correlated with the warm Greenland interstadial 25 (GI 25), whereas the weak monsoonal event is related to the cold Greenland stadial 25 within dating errors. The GI 25 monsoonal event registered in our record is also documented in various published time series from different regions of China. The lines of evidence indicate that this event occurred over the entirety of monsoonal China and was also broadly antiphase, similar to the corresponding event on a millennial time scale in the South American monsoon territory. In our record, one 700 yr weak monsoon event at 110.7 +0.6 −0.5 to 110.0 +0.8 −0.4 ka divides the GI 25 into three substages. These multicentennial to millennial–scale monsoon events correspond to two warm periods and an intervening cold interval for the intra-interstadial climate oscillations within GI 25, thus supporting a persistent coupling of the high- and low-latitude climate systems over the last glacial period.